The development of students' collaborative competence in foreign language studies at tertiary level - Artamonova, Anna; University of Latvia (My University, 2006)
Contents : Introduction 1. The Pedagogical Basis of the Development of Students' Collaborative Competence 1.1. Competence as a Factor of Students' Future Professional Development in their Foreign Language Study 1.2. The Essence of Collaboration, Cooperation, and Communication: Comparative Aspect 1.3. The Essence and Structure of Students' Collaborative Competence 1.3.1. The Analysis of Communicative Competence 1.3.2. The Analysis of Intercultural Competence 1.3.3. The Analysis of Transactional Competence 1.3.4. The Analysis of Cooperative Competence 2. Research-Based Collaborative Foreign Language Study as a Means of the Development of Students' Collaborative Competence 2.1. The Essence of Collaborative Foreign Language Study 2.2. The Characteristic Features of Collaborative Foreign Language Study 2.3. The Analysis of the Functional Model of Research-Based Collaborative Foreign Language Study 2.4. A Means of the Development of Students' Collaborative Competence in Foreign Language Study 2.5. The Development of Students' Collaborative Competence in Foreign Language Study 2.5.1. The Identification of the Initial Level of Students' Collaborative Competence (the Control Experiment) 2.5.2. The Development of Students' Collaborative Competence (the Formative Experiment) 2.6. The Analysis of the Results of the Development of Students' Collaborative Competence Conclusions Bibliography A List of Tables A List of Figures A List of Questionnaires A List of Pie-charts and Bar-charts A List of Diagrams Appendices I-VI
Studentu kolaboratīvās kompetences veidošanās svešvalodu studijās augstskolā
Advisor: Kramiņa, Ingrīda
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Augstākā izglītība; Svešvalodu apguve; Grupu darbs izglītībā; Komunikatīvā kompetence; Komunikācija izglītībā; Kolaboratīvā kompetence; Foreign language study; Collaborative competence; Communicative competence